Cointegration test on ASEAN currencies before and during the currency turmoil - Fauzias Mat Nor,; Noor Azuddin Yakob,; Zaidi Isa, (Penerbit Universiti Kebangsaan Malaysia, 2000)
The impact of the Southeast Asian currency turmoil on some ASEAN countries demonstrates the need to understand the regional currency movements. In view of the growing interest in the Southeast Asian currency turmoil, this paper investigates the relationship between the main ASEAN currencies namely, Thai Bhat, Malaysian Ringgit, Singapore Dollar, Indonesia Rupiah and the Philipines Peso by applying the cointegration test to determine the long run dynamics between the currencies. The causality test is also performed to determine the influence of each currency on each other. The results show that the currencies are non-stationary and at most there are four cointegrating vectors for the periods before and during the turmoil. The Granger causality test shows that Malaysian currency seems to have the most significant causalities on the ASEAN currencies during the turmoil. However, the variance decomposition and the multivariate vector autoregression reveal that the past information of each currency contributed the most to its forecast error